Birokrasi di Industri Pariwisata Indonesia: Kendala dan Upaya Perbaikannya - Sarjito, Aris (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2025)
The Indonesian tourism industry is vital to the country's economy, yet it grapples with bureaucratic constraints hindering its growth. This study aims to analyze bureaucratic structures, processes, and improvement efforts within the Indonesian tourism sector. Employing qualitative research methods using secondary data, the study examines the understanding of bureaucratic structures, the impact of inefficiencies on businesses and investment, improvement efforts, and actionable recommendations for enhancing tourism development. Findings reveal complex bureaucratic processes governed by institutional norms and policy implementations. Inefficiencies, such as lengthy permitting procedures and regulatory inconsistencies, deter investment and disrupt business operations. Improvement efforts include policy diffusion, innovation diffusion, inter-agency coordination, regulatory reforms, and public-private partnerships. Actionable recommendations emphasize the importance of collaboration, regulatory reforms, capacity-building initiatives, and publicprivate partnerships to streamline bureaucracy and foster tourism development in Indonesia. This research contributes to a deeper understanding of bureaucratic dynamics in the Indonesian tourism industry and offers insights for policymakers, industry stakeholders, and researchers